The Potential of Biology Learning in Education Context in Industrialized Agricultural Areas - Siswati , Bea Hana (Research Highlights in Language, Literature and Education Vol. 9, 2023)
Biology learning in industrial agricultural areas has unique characteristics that are not shared by other areas. It is important to analyze the learning potential of schools in industrial agricultural areas. The analysis was done by reviewing the literature and reviewing research that has been done by previous researchers. The research method in this article is a literature review. The literature review was conducted based on predetermined inclusion and exclusion criteria. The research included in the review relate to biology subjects. The results of the literature review revealed that the use of appropriate learning strategies will have a good impact on biology learning. This also applies to learning media used by teachers, which will be able to empower student learning outcomes and thinking skills. By optimizing biology learning using learning strategies and certain learning media, it is hoped that it can form future generations who have good quality and are competent in their fields.